Nanomedicines in diagnosis and treatment of prostate cancers: an updated review - Wang, Jiajia; Zhang, Xuan; Xing, Jiazhen; Gao, Lijian; Lu, Hua (Frontiers in Bioengineering and Biotechnology, 2024)
Prostate cancer (PC) is the third most common male cancer in the world, which occurs due to various mutations leading to the loss of chromatin structure. There are multiple treatments for this type of cancer, of which chemotherapy is one of the most important. Sometimes, a combination of different treatments, such as chemotherapy, radiotherapy, and surgery, are used to prevent tumor recurrence. Among other treatments, androgen deprivation therapy (ADT) can be mentioned, which has had promising results. One of the drawbacks of chemotherapy and ADT treatments is that they are not targeted to the tumor tissue. For this reason, their use can cause extensive side effects. Treatments based on nanomaterials, known as nanomedicine, have attracted much attention today. Nanoparticles (NPs) are one of the main branches of nanomedicine, and they can be made of different materials such as polymer, metal, and carbon, each of which has distinct characteristics. In addition to NPs, nanovesicles (NVs) also have therapeutic applications in PC. In treating PC, synthetic NVs (liposomes, micelles, and nanobubbles) or produced from cells (exosomes) can be used. In addition to the role that NPs and NVs have in treating PC, due to being targeted, they can be used to diagnose PC and check the treatment process. Knowing the characteristics of nanomedicine-based treatments can help design new treatments and improve researchers' understanding of tumor biology and its rapid diagnosis. In this study, we will discuss conventional and nanomedicine-based treatments. The results of these studies show that the use of NPs and NVs in combination with conventional treatments has higher efficacy in tumor treatment than the individual use of each of them.